1990
DOI: 10.1073/pnas.87.18.6929
|View full text |Cite
|
Sign up to set email alerts
|

Synporins--synthetic proteins that emulate the pore structure of biological ionic channels.

Abstract: A class of proteins that mimic the fundamental pore structure of authentic ionic channels has been designed, synthesized, and characterized. The design is based on our earlier result that a 23-mer peptide with the sequence of the M2 segment of the Torpedo californica acetylcholine receptor 8 subunit-Glu-Lys-Met-Ser-Thr-Ala-Ile-Ser-Val-Leu-Leu-AlaGln-Ala-Val-Phe-Leu-Leu-Leu-Thr-Ser-Gln-Arg-forms cation-selective channels in lipid bilayers, presumably by selfassembly of conductive oligomers. Accordingly, a tethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 22 publications
2
54
0
Order By: Relevance
“…species observed with BoTxATM, both in amplitude and in the time that the channels remain open, is anticipated for an amphipathic peptide that self-assembles in the membrane to form noncovalent conductive oligomers of different sizes (Oiki et al, 1988(Oiki et al, , 1990Montal et al, 1990;cf. Montal, 1995).…”
Section: Channel Formation By Botxatmmentioning
confidence: 86%
See 1 more Smart Citation
“…species observed with BoTxATM, both in amplitude and in the time that the channels remain open, is anticipated for an amphipathic peptide that self-assembles in the membrane to form noncovalent conductive oligomers of different sizes (Oiki et al, 1988(Oiki et al, , 1990Montal et al, 1990;cf. Montal, 1995).…”
Section: Channel Formation By Botxatmmentioning
confidence: 86%
“…Molecular modeling, energy minimization, and molecular dynamics simulations, were conducted on a Silicon Graphics IRIS 4D/210 GTXB workstation using the INSIGHT and DIS-COVER molecular modeling packages of Biosym (San Diego, California) (Oiki et al, 1990;Montal et al, 1990Montal et al, , 1992. Lowenergy arrangements of a-helices and four-helix bundles were calculated with semiempirical potential energy functions and optimization routines.…”
Section: Con Formational Energy Computationsmentioning
confidence: 99%
“…Several synthetic, putative transmembrane segments of natural channel proteins as well as synthetic amphiphilic peptides have been investigated for the purpose of modeling ion channels (Oiki et al, 1988(Oiki et al, , 1990Langosch et al, 1991;Ghosh and Stroud, 1991;Lear et al, 1988;DeGrado and Lear, 1990;Montal et al, 1990). Taking these results and ours into account, it is tempting to suggest that only those peptides which, by molecular modeling, show perfect steric arrangements in the helical bundles, also show defined channel-current fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…Examples which would fit into this model are the 21-amino-acid peptides composed of repeats of leucines and serines (LSSLLSL),, or an analog with an Aib (a) substitution (LSLaLSL), (Lear et al, 1988;DeGrado and Lear, 1990). On the other hand, synthetic peptides with sequences of the MA segment and the transmembrane M2 segment of the n-AcChoR and the M2 of glycine receptor channels, as well as of the S3 segment of the voltage-gated sodium channel, form channels with variable-conductance states (Oiki et al, 1988;Langosch et al, 1991;Ghosh and Stroud, 1991;Montal et al, 1990). According to the published channel models (Oiki et al, 1990), these peptides do not seem to assemble as perfectly to helix bundles as do those of Lear et al (1988) or ours.…”
Section: Discussionmentioning
confidence: 99%
“…closed times; t,, open times homo-oligomer of five amphipathic a-helices arranged such that polar residues line a central hydrophilic pathway and apolar residues face the hydrophobic bilayer interior [l 11. We have demonstrated that a four-helix bundle protein designated as T,M26, in which four identical helical modules with the sequence of M26 were covalently attached to a multifunctional carrier (template) [25,26], forms ionic channels in lipid bilayers. The T,M26 channel is cation-selective and blocked by mM concentrations of the local anesthetic channel blocker QX-22, properties that are characteristic of the AChR channel [25].…”
Section: Introductionmentioning
confidence: 99%